2019
DOI: 10.1590/1413-81232018245.14232017
|View full text |Cite
|
Sign up to set email alerts
|

Description of suicide ideation among older adults and a psychological profile: a cross-sectional study in Turkey

Abstract: This study investigates the suicidal ideation and the possible causes for suicidal behaviour in the elderly. Subjects were 150 patients aged 65 and older who were evaluated using the sociodemographic data collection forms, Geriatric Depression Scale (GDS), Suicidal Ideation Scale (SIS), Reasons for Living Inventory (RLI), and Beck Hopelessness Scale (BHS). Of 150 patients, 72.7% were women and 27.3% were men, ages ranged from 65 to 88 years. Suicidal ideation was noted in 30.7% of patients. When the mean of BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…To date, several risk factors of suicidal thoughts and behavior have been identified among older adults, and include factors such as mental health complications, sleep problems, mobility problems, lower quality of life, and severe functional impairment [7][8][9][10][11][12][13][14][15]. One other potential but under-studied risk factor in older adults is that of visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several risk factors of suicidal thoughts and behavior have been identified among older adults, and include factors such as mental health complications, sleep problems, mobility problems, lower quality of life, and severe functional impairment [7][8][9][10][11][12][13][14][15]. One other potential but under-studied risk factor in older adults is that of visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the level of education was negatively associated with a higher risk of suicide behaviour engagement ( i.e. , suicidal ideation and attempt), as Aslan et al [ 3 ] reported.…”
Section: Resultsmentioning
confidence: 93%
“…Most studies (60%) selected examined suicidal ideation outcome[ 3 , 10 , 20 - 22 , 25 , 36 , 38 - 52 ]. On the other hand, suicide attempt was assessed in 40% of studies[ 2 , 3 , 21 , 35 , 37 , 41 , 44 , 52 - 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority emphasized the need to promote public policies for the care of mental health problems resulting from violence such as depression, aggressive behavior, and suicidal ideation and suicide attempts. Violence against elderly persons was highlighted in the issue of suicide and attempted suicide, with a study in Turkey 39 . Two studies from Latin American and Caribbean addressed political violence and the effects of armed conflicts on the population's mental health.…”
Section: Analysis Of Specific Themes and Subthemesmentioning
confidence: 99%